College students’ knowledge of hostels and what factors influence their intent to stay - Edwards, Gavin (Kansas State University, 2012)
Hostels play a significant role in the lodging industry throughout the world and even in some locations in the United States (U.S.). However, in many places in the U.S. hostels have yet to be introduced. They have the potential to offer budget lodging accommodation, but hotels and motels remain the most popular forms of lodging. This study investigated the perceptions of Kansas State University (KSU) students about hostels and their intent to use hostels. A focus group was used to gain insight into students’ perceptions of hostels and aided in the development of a written survey. An online survey was used to gather information from KSU students. It was sent to a randomly selected sample of 5,000 KSU students. There was a response rate of 8% (n=401). Respondents knew about hostels and were willing to stay in them. A factor analysis was conducted on 31 characteristics of hostels that might be important to hostel users and it was determined that these items could be reduced to three factors: Safety and Amenities ([alpha]=.92); Location and Socializing([alpha]=.91); and Accommodations ([alpha]=.60). Safety and Amenities had the highest mean scores for individual items in the factor while Accommodations had the lowest. Multiple linear regression was used to determine if the three factors would predict KSU students’ intent to stay in a hostel. The regression model was significant (p[less than or equal to].000) and all three factors were significant. The model had an R Square of .31. A t-test was used to determine if males and females differed in intent to stay in a hostel, Safety and Amenities, Location and Socializing, and Accommodation. Females had higher mean scores for Safety and Amenities and Location and Socializing than did males. This study showed that college students would stay in a hostel. Hostel owners/operators and hostel organizations can use this information to better market their hostel and it will help them to determine which amenities they will need to have to meet customer demands. Research should be conducted with a larger and more geographically diverse sample to determine if the results can be generalized beyond KSU students. Research with actual hostel users will help to determine characteristics they think are important and to compare results with this study.
Keywords: Hostels; College students; Recreation and Tourism (0814)